Climate teleconnections synchronize Picea glauca masting and fire disturbance: Evidence for a fire‐related form of environmental prediction. (8th November 2019) - Ascoli, Davide; Hacket‐Pain, Andrew; LaMontagne, Jalene M.; Cardil, Adrián; Conedera, Marco; Maringer, Janet; Motta, Renzo; Pearse, Ian S.; Vacchiano, Giorgio
Abstract: Synchronous pulses of seed masting and natural disturbance have positive feedbacks on the reproduction of masting species in disturbance‐prone ecosystems. We test the hypotheses that disturbances and proximate causes of masting are correlated, and that their large‐scale synchrony is driven by similar climate teleconnection patterns at both inter‐annual and decadal time scales. Hypotheses were tested on white spruce ( Picea glauca ), a masting species which surprisingly persists in fire‐prone boreal forests while lacking clear fire adaptations. We built masting, drought and fire indices at regional (Alaska, Yukon, Alberta, Quebec) and sub‐continental scales (western North America) spanning the second half of the 20th century. Superposed Epoch Analysis tested the temporal associations between masting events, drought and burnt area at the regional scale. At the sub‐continental scale, Superposed Epoch Analysis tested whether El Niño‐Southern Oscillation (ENSO) and its coupled effects with the Atlantic Multidecadal Oscillation (AMO) in the positive phase (AMO+/ENSO+) synchronize drought, burnt area and masting. We additionally tested the consistency of our synchronization hypotheses on a decadal temporal scale to verify whether long‐term oscillations in AMO+/ENSO+ are coherent to decadal variation in drought, burnt area and masting. Analyses demonstrated synchronicity between drought, fire and masting. In all regions the year before a mast event was drier and more fire‐prone than usual. During AMO+/ENSO+ events sub‐continental indices of drought and burnt area experienced significant departures from mean values. The same was observed for large‐scale masting in the subsequent year, confirming 1‐year lag between fire and masting. Sub‐continental indices of burnt area and masting showed in‐phase decadal fluctuations led by the AMO+/ENSO+. Results support the 'Environmental prediction hypothesis' for mast seeding. Synthesis . We provide evidence of large‐scale synchronicity between seed masting in Picea glauca and fire regimes in boreal forests of western North America at both inter‐annual and decadal time scales. We conclude that seed production in white spruce predicts changes in disturbance regimes by sharing the same large‐scale climate drivers with drought and fire. This gives new insides in a mechanism providing a fire‐sensitive species with higher than expected adaptability to changes in climate. Abstract : We provide evidence of large‐scale synchronicity between seed masting in Picea glauca and fire regimes in boreal forests of western North America at both inter‐annual and decadal time scales. We conclude that seed production in white spruce predicts changes in disturbance regimes by sharing the same large‐scale climate drivers with drought and fire. This gives new insides in a mechanism providing a fire‐sensitive species with higher than expected adaptability to changes in climate. Foreign Language Abstract French Abstract: La synchronization du masting des semis et des perturbations naturelles ont un effet positif sur la reproduction d'espèces à fructification irrégulière dans des écosystèmes sensibles aux perturbations. Dans cette étude, on a testé les hypothèses qu'il existait une corrélation entre les perturbations et les causes ultimes du masting et que leurs synchronizations à grande échelle était dû à des patrons de téléconnections climatiques similaires, aux échelles décennales et interannuelles. L'espèce cible choisie pour tester cette hypothèse est l'épinette blanche (Picea glauca) une espèce à fructification irrégulière qui inopinément réussit à survivre dans les forêts boréales de l'Amérique du nord. On a créé des indices de masting, de sécheresse et de feux de forêt à des échelles régionales (Alaska, Yukon, Alberta, Québec) et subcontinental (Nord‐ouest de l'Amérique du nord) pour la deuxième moitié du XX siècle. L'association temporelle à l'échelle régionale entre masting, sécheresse et feux a été testée par le biais d'une analyse par époques superposées (Superposed Epoch Analysis). Au niveau subcontinental, la Superposed Epoch Analysis a été utilisée pour tester si la ENSO (El Niño‐Southern Oscillation) et ses effets cumulatifs avec l'AMO (Oscillation Atlantique Multi décennale) pendant des phases positives (AMO+/ENSO+) synchronisent le masting, la sécheresse et les feux. La constance de ses synchronizations a été testée sur une échelle temporelle décennale pour vérifier si les oscillations AMO+/ENSO+ sur le long terme étaient cohérente avec les variations des sécheresses, des surfaces brulées et du masting. Les analyses ont révélé la synchronization entre sécheresse, feux et masting. Dans toutes les régions, l'année qui précède un phénomène de masting a été sèche et plus propice aux incendies que d'habitude. Pendent les épisodes AMO+/ENSO+, les indices de sécheresse et de surface brulée à l'échelle subcontinentale ont montré des valeurs hors de la moyenne. De même, les phénomènes de masting à large échelle qui ont eu lieu dans l'année suivante, confirment le décalage d'un an entre les feux et la production de semis. Les résultats supportent l'hypothèse d'une prédiction environnementale ( Environmental prediction hypothesis ) pour le masting comme démontré avec la fluctuation parallèle sur une échelle décennale de la surface brûlée et du masting au niveau subcontinentale. En synthèse, on a prouvé la synchronisation à grande échelle entre les événements de masting de Picea glauca et le régime des feux de couronne dans les forêts boréales du nord‐ouest de l'Amérique du nord, que ce soit à des rythmes interannuelles ou décennales. La production abondante de semis chez l'épinette blanche, étant stimulée par les mêmes facteurs qui règlent la sécheresse et les incendies, suit donc les changements du régime des perturbations. Cela nous donnent de nouvelles connaissances sur un mécanisme qui permet à une espèce sensible au feu d'avoir un potentiel d'adaptation au changement climatique plus haut que prévu.